The role of cover soil properties in steering reclamation ecohydrology - Owen F. Sutton; Hilary Irving; James H. Sherwood; Jonathan S. Price (Ecological Engineering, 2026)

Past trajectory of a Northwest Europe socio-ecosystem at the land-sea interface: Case study of the northern watersheds of the Bay of Brest over the last 150 years - C. Valero; A. Penaud; M. Vidal; E. Goubert; P.A. Dessandier; S. Schmidt; E. Glémarec; P. Brigode; L. Bosseboeuf; Y.M. Paulet; J. Sutton; P. Ailliot; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

GOOS Essential Ocean Variables: the backbone of a sustained and evolving global ocean observing system - Belén Martín Míguez; Emma Heslop; Narissa Bax; Lisandro Benedetti-Cecchi; Gabrielle Canonico; Kim Currie; Karen Evans; Albert S. Fischer; Véronique Garçon; Maria Hood; Johannes Karstensen; Ana Lara-López; et al. (Frontiers in Marine Science, 2026)
The need for ocean information has never been greater. From climate change to food security and extreme events, we need to understand the role of the ocean and better predict change and impact. This is only possible with the sustained collection of a key set of ocean observations. The Global Ocean Observing System (GOOS) coordinates international efforts to collect these Essential Ocean Variables (EOVs), which span physics, biogeochemistry, biology and ecosystem realms. Guided by three expert panels, these EOVs are used to define the needs and design of a sustained, fit for purpose global ocean observing system, aimed at maximizing investments in observing infrastructure. As the GOOS EOVs are increasingly used, it has become important to discuss and refine the understanding of this framework, to ensure that the right balance is struck between their essential nature and the need to expand to new domains and integrate with key global policies. In this paper we provide a description of the EOV framework, discuss some of the challenges in implementing it, and identify a set of recommendations for GOOS and the ocean observing community to take forward. These recommendations include increasing the transparency of the EOV adoption process, and the need to periodically assess the EOVs in consultation with observing communities and with the entities managing other global essential variable frameworks in cross cutting realms such as climate and biodiversity. This will contribute to building a useful and responsive global ocean observing system that delivers the observations required to meet societal needs.

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Grief Among Oncology Providers: Prevalence and Association with Burnout - Shannon R. McGue; Cameron J. Oswalt; Benjamin T. Berger; Sarah S. Morgan; Sara A. Barlow; Carl F. Pieper; Linda M. Sutton; Matthew K. Labriola; Anthony N. Galanos (Journal of Cancer Education, 2025)

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

Incorporating buccal mass planar mechanics and anatomical features improves neuromechanical modeling of Aplysia feeding behavior - Michael J. Bennington; Ashlee S. Liao; Ravesh Sukhnandan; Bidisha Kundu; Stephen M. Rogers; Jeffrey P. Gill; Jeffrey M. McManus; Gregory P. Sutton; Hillel J. Chiel; Victoria A. Webster-Wood (Biological Cybernetics, 2025)
To understand how behaviors arise in animals, it is necessary to investigate both the neural circuits and the biomechanics of the periphery. A tractable model system for studying multifunctional control is the feeding apparatus of the marine mollusk Aplysia californica . Previous in silico and in roboto models have investigated how the nervous and muscular systems interact in this system. However, these models are still limited in their ability to match in vivo data both qualitatively and quantitatively. We introduce a new neuromechanical model of Aplysia feeding that combines a modified version of a previously developed neural model with a novel biomechanical model that better reflects the anatomy and kinematics of Aplysia feeding. The model was calibrated using a combination of previously measured biomechanical parameters and hand-tuning to behavioral data. Using this model, simulated feeding experiments were conducted, and the resulting behavioral metrics were compared to animal data. The model successfully produces three key behaviors seen in Aplysia and demonstrates a good quantitative agreement with biting and swallowing behaviors. Additional work is needed to match rejection behavior quantitatively and to reflect qualitative observations related to the relative contributions of two key muscles, the hinge and I3. Future improvements will focus on incorporating the effects of deformable 3D structures in the simulated buccal mass.

Separation of virus-like particles and nano-emulsions for vaccine development by Capillary Zone Electrophoresis - Yousef S. Elshamy; Caleb Kinsey; Richard R. Rustandi; Adam T. Sutton (Analytica Chimica Acta, 2025)

Effects of snake fungal disease (ophidiomycosis) on the skin microbiome across two major experimental scales - Alexander S. Romer; Matthew Grisnik; Jason W. Dallas; William Sutton; Christopher M. Murray; Rebecca H. Hardman; Tom Blanchard; Ryan J. Hanscom; Rulon W. Clark; Cody Godwin; N. Reed Alexander; Kylie C. Moe; et al. (Conservation Biology, 2025)
Emerging infectious diseases are increasingly recognized as a significant threat to global biodiversity conservation. Elucidating the relationship between pathogens and the host microbiome could lead to novel approaches for mitigating disease impacts. Pathogens can alter the host microbiome by inducing dysbiosis, an ecological state characterized by a reduction in bacterial alpha diversity, an increase in pathobionts, or a shift in beta diversity. We used the snake fungal disease (SFD; ophidiomycosis), system to examine how an emerging pathogen may induce dysbiosis across two experimental scales. We used quantitative polymerase chain reaction, bacterial amplicon sequencing, and a deep learning neural network to characterize the skin microbiome of free‐ranging snakes across a broad phylogenetic and spatial extent. Habitat suitability models were used to find variables associated with fungal presence on the landscape. We also conducted a laboratory study of northern watersnakes to examine temporal changes in the skin microbiome following inoculation with Ophidiomyces ophidiicola . Patterns characteristic of dysbiosis were found at both scales, as were nonlinear changes in alpha and alterations in beta diversity, although structural‐level and dispersion changes differed between field and laboratory contexts. The neural network was far more accurate (99.8% positive predictive value [PPV]) in predicting disease state than other analytic techniques (36.4% PPV). The genus Pseudomonas was characteristic of disease‐negative microbiomes, whereas, positive snakes were characterized by the pathobionts Chryseobacterium , Paracoccus , and Sphingobacterium . Geographic regions suitable for O. ophidiicola had high pathogen loads (>0.66 maximum sensitivity + specificity). We found that pathogen‐induced dysbiosis of the microbiome followed predictable trends, that disease state could be classified with neural network analyses, and that habitat suitability models predicted habitat for the SFD pathogen.

Seasonality and hydroclimatic variability shape the functional and taxonomic diversity of nearshore fish communities in glacierized estuaries of Alaska - Lauren Sutton; Brian P. Ulaski; Nina C. Lundstrom; Emily J. Whitney; Jason B. Fellman; Anne H. Beaudreau; Jordan Jenckes; Scott S. Gabara; Brenda Konar (Journal of Experimental Marine Biology and Ecology, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P06-10 NGS-based discovery of circulating microRNA biomarkers of drug-induced pancreatic injury (DIPI) - P. Szatmary; A. Evans; A. Jones; D. Latawiec; W. Cai; A. Kattakayam; C. Goldring; G. Beyer; S. Sirtl; I. Alvarez-Alvarez; W. Bailey; B. Ackermann; et al. (Toxicology Letters, 2024)

New, dated small impacts on the South Polar Layered Deposits (SPLD), Mars, and implications for shallow subsurface properties - M.E. Landis; C.M. Dundas; A.S. McEwen; I.J. Daubar; P.O. Hayne; S. Byrne; S.S. Sutton; V.G. Rangarajan; L.L. Tornabene; A. Britton; K.E. Herkenhoff (Icarus, 2024)

The high-resolution imaging science experiment (HiRISE) in the MRO extended science phases (2009–2023) - A.S. McEwen; S. Byrne; C. Hansen; I.J. Daubar; S. Sutton; C.M. Dundas; N. Bardabelias; N. Baugh; J. Bergstrom; R. Beyer; K.M. Block; V.J. Bray; et al. (Icarus, 2024)

Polar science results from Mars Reconnaissance Orbiter: Multiwavelength, multiyear insights - M.E. Landis; P.J. Acharya; N.R. Alsaeed; C. Andres; P. Becerra; W.M. Calvin; E.M. Cangi; S.F.A. Cartwright; M.S. Chaffin; S. Diniega; C.M. Dundas; C.J. Hansen; et al. (Icarus, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

FDA-approved disulfiram as a novel treatment for aggressive leukemia - Mawar Karsa; Lin Xiao; Emma Ronca; Angelika Bongers; Dayna Spurling; Ayu Karsa; Sandra Cantilena; Anna Mariana; Tim W. Failes; Greg M. Arndt; Laurence C. Cheung; Rishi S. Kotecha; et al. (Journal of Molecular Medicine, 2024)
Acute leukemia continues to be a major cause of death from disease worldwide and current chemotherapeutic agents are associated with significant morbidity in survivors. While better and safer treatments for acute leukemia are urgently needed, standard drug development pipelines are lengthy and drug repurposing therefore provides a promising approach. Our previous evaluation of FDA-approved drugs for their antileukemic activity identified disulfiram, used for the treatment of alcoholism, as a candidate hit compound. This study assessed the biological effects of disulfiram on leukemia cells and evaluated its potential as a treatment strategy. We found that disulfiram inhibits the viability of a diverse panel of acute lymphoblastic and myeloid leukemia cell lines ( n = 16) and patient-derived xenograft cells from patients with poor outcome and treatment-resistant disease ( n = 15). The drug induced oxidative stress and apoptosis in leukemia cells within hours of treatment and was able to potentiate the effects of daunorubicin, etoposide, topotecan, cytarabine, and mitoxantrone chemotherapy. Upon combining disulfiram with auranofin, a drug approved for the treatment of rheumatoid arthritis that was previously shown to exert antileukemic effects, strong and consistent synergy was observed across a diverse panel of acute leukemia cell lines, the mechanism of which was based on enhanced ROS induction. Acute leukemia cells were more sensitive to the cytotoxic activity of disulfiram than solid cancer cell lines and non-malignant cells. While disulfiram is currently under investigation in clinical trials for solid cancers, this study provides evidence for the potential of disulfiram for acute leukemia treatment. Key messages Disulfiram induces rapid apoptosis in leukemia cells by boosting oxidative stress. Disulfiram inhibits leukemia cell growth more potently than solid cancer cell growth. Disulfiram can enhance the antileukemic efficacy of chemotherapies. Disulfiram strongly synergises with auranofin in killing acute leukemia cells by ROS induction. We propose testing of disulfiram in clinical trial for patients with acute leukemia.

Degradation of the 2014–2015 Holuhraun vent-proximal edifice in Iceland - S. S. Sutton; J. A. Richardson; P. L. Whelley; S. P. Scheidt; C. W. Hamilton (Bulletin of Volcanology, 2024)
The earliest stages of volcanic vent degradation are rarely measured, leaving a gap in the knowledge that informs landform degradation models of cinder cones and other monogenetic vent structures. We documented the initial degradation of a 500-m-long spatter rampart at the primary vent of the 2014–2015 Holuhraun eruption in northern Iceland with high-resolution topographic change maps derived from terrestrial laser scanning (TLS) and photogrammetric surveys using an unoccupied aircraft system (UAS). Topographic differencing shows a total negative volume change of 42,637 m 3 , and a total positive volume change (basal deposition) of 10,304 m 3 (primarily as deposition at the base of steeply sloping surfaces). Two distinct styles of volume changes were observed on the interior and exterior of the spatter rampart. Material on the interior of the vent was removed from oversteepened slopes by discrete rockfalls, while diffusive processes were qualitatively evident on the exterior slopes. We propose a novel conceptual landform evolution model for spatter ramparts that combines rockfall processes on the interior walls, diffusive gravitational sliding on the exterior slopes, and incorporates cooling contraction and compaction over the entire edifice to describe the observed modes of topographic change during the onset of degradation. Potential hazards at fresh spatter ramparts are rockfalls at high slope areas of the vent interior walls where contacts between spatter clasts are prone to weakening by fumarolic activity, weathering, and settling. To capture such hazards, our data suggest a cadence for monitoring changes yearly for the first few years post-eruption, and at longer intervals thereafter.

Monarch Butterfly (Danaus plexippus) Roost Site-Selection Criteria and Locations East of the Appalachian Mountains, U.S.A. - Brandon M. Boxler; Cynthia S. Loftin; William B. Sutton (Journal of Insect Behavior, 2024)

Standardizing gross descriptions of skin lesions in common bottlenose dolphins (Tursiops truncatus) stranded in Southwest Florida, 2015–2019 - Ruth Y. Ewing; Meghan N. Sutton; Hada M. Herring; Molly R. Schubert; Denise M. Boyd; Jill L. Richardson; David S. Rotstein (Frontiers in Marine Science, 2023)
As the first line of defense, the integumentary system is critical in comprehensively evaluating dolphin morbidity during stranding response. Most published studies on skin lesions in bottlenose dolphins (Tursiops truncatus) lack standardized gross descriptions and methodologies for evaluating lesions. The primary objective of this study was to evaluate the effectiveness of an assessment matrix designed to consistently describe skin lesions based on a set of standardized gross description characteristics. The matrix was implemented by reviewing necropsy reports, histopathology reports, and photographs collected from bottlenose dolphins stranded in Southwest Florida from 2015 through 2019. Of the 32 dolphins that met the inclusion criteria, 19 presented with skin lesions and five reviewers described each of the 46 lesions according to a novel, standardized assessment matrix. The most common descriptor selected, in each of the respective matrix categories, were, by anatomic location, head; distribution, multifocal to coalescing; quantity, moderate (10–30); size, <2 cm; shape, punctate; margin, rounded; color modifier, hyperpigmentation; texture, smooth; and texture modifier, flat. These prevalent descriptors coincided with the frequent occurrence of histologically described hydropic degeneration (n=7, 15.2%) and were confirmed poxviral lesions in 6.52% (n=3). Identifying lesion patterns using standardized descriptors capitalizes on the unique pathogen tissue tropism and the implementation of certain disease mechanisms in the integumentary system. Therefore, it can facilitate differential disease diagnoses and guide ancillary diagnostics testing. The use of standardized descriptors will aid in etiologic identification and monitoring of skin lesions and associated diseases, advancing our understanding of dolphin morbidity and mortality.

Cetacean‐mediated vertical nitrogen transport in the oceanic realm - Matthew S. Woodstock; Jeremy J. Kiszka; M. Rafael Ramírez‐León; Tracey T. Sutton; Katja Fennel; Bin Wang; Yuying Zhang (Limnology and Oceanography, 2023)
In natural systems, animal‐mediated nutrient transport can be a major driver of primary productivity, but the role of marine megafauna such as cetaceans in mediating the transfer and recycling of nutrients has been overlooked. Here, we developed a spatially resolved, stochastic, nutrient‐transport model for cetaceans in the oceanic Gulf of Mexico using species−specific foraging depths, distributions, and diets. An estimated 6.4 × 10 8 mmol N d −1 , or 0.06 mt N yr −1 ind −1 , is transported to the surface from depths below 100 m by the 19 cetacean species that occur in the oceanic Gulf of Mexico; 75% of this transport occurs seaward of the continental slope, but the per area transported nitrogen is greater on the continental slope (200–1000 m) than in the ocean basin. Benthos to surface transport comprised 6.0 × 10 7 mmol N d −1 and was much more common on the continental slope than the open basin. Compared to an existing physical‐biogeochemical model, the transported nutrients add 8% N d −1 to the estimated ammonium concentration above the nutricline and could add 16% N d −1 to the surface ammonium concentration if expelled nutrients remain at the surface. Through feeding on diel vertical migrants, cetaceans retain an additional 2.7 × 10 7 mmol N d −1 in the surface waters that would otherwise return to depth via downward diel vertical migration. Cetaceans contribute to nutrient movements and recycling in the oceanic Gulf of Mexico, and may provide one of the few allochthonous sources of nutrients for primary producers in oligotrophic ecosystems.

Blue carbon pathways for climate mitigation: Known, emerging and unlikely - Jennifer Howard; Ariana E. Sutton-Grier; Lindsey S. Smart; Christian C. Lopes; Jill Hamilton; Joan Kleypas; Stefanie Simpson; Jennifer McGowan; Albert Pessarrodona; Heidi K. Alleway; Emily Landis (Marine Policy, 2023)

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Vulnerability and resilience of living marine resources to the Deepwater Horizon oil spill: an overview - Steven A. Murawski; Patrick T. Schwing; William F. Patterson; Tracey T. Sutton; Paul A. Montagna; Rosanna J. Milligan; Samantha B. Joye; Len Thomas; Joshua P. Kilborn; Claire B. Paris; Robin Faillettaz; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The 2010 Deepwater Horizon (DWH) oil well blowout in the Gulf of Mexico (GoM) was the largest and perhaps most consequential accidental marine oil spill in global history. This paper provides an overview of a Research Topic consisting of four additional papers that: (1) assemble time series data for ecosystem components in regions impacted by the spill, and (2) interpret temporal changes related to the vulnerability of species and ecosystems to DWH and the ensuing resilience to perturbation. Time series abundance data for many taxa pre-date DWH, often by decades, thus allowing an assessment of population- and community-level impacts. We divided the north central GoM into four interconnected “eco-types”: the coastal/nearshore, continental shelf, open-ocean pelagic and deep benthic. Key taxa in each eco-type were evaluated for their vulnerability to the circumstances of the DWH spill based on population overlap with oil, susceptibility to oil contamination, and other factors, as well their imputed resilience to population-level impacts, based on life history metrics, ecology and post-spill trajectories. Each taxon was scored as low, medium, or high for 13 vulnerability attributes and 11 resilience attributes to produce overall vulnerability and resilience scores, which themselves were also categorical (i.e., low, medium, or high). The resulting taxon-specific V-R scores provide important guidance on key species to consider and monitor in the event of future spills similar to DWH. Similar analyses may also guide resource allocation to collect baseline data on highly vulnerable taxa or those with low resilience potential in other ecosystems. For some species, even a decade of observation has been insufficient to document recovery given chronic, long-term exposure to DWH oil remaining in all eco-types and because of impacts to the reproductive output of long-lived species. Due to the ongoing threats of deep-water blowouts, continued surveillance of populations affected by DWH is warranted to document long-term recovery or change in system state. The level of population monitoring in the open-ocean and deep benthic eco-types has historically been low and is inconsistent with the continued migration of the oil industry to the ultra-deep (≥1,500 m) where the majority of leasing, exploration, and production now occurs.

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Body size, depth of occurrence, and local oceanography shape trophic structure in a diverse deep-pelagic micronekton assemblage - Travis M. Richards; Tracey T. Sutton; Matthew S. Woodstock; Heather Judkins; R.J. David Wells (Progress in Oceanography, 2023)

HPV Knowledge Retention and Concurrent Increase in Vaccination Rates 1.5 Years After a Novel HPV Workshop in Medical School - Sarah Sutton; Shaghauyegh S. Azar; Lauran K. Evans; Ariel Murtagh; Catherine McCarthy; Maie St. John (Journal of Cancer Education, 2023)

The diagnostic utility of hypophosphatemia for differentiating generalized tonic-clonic seizures from syncope in dogs: A case control study - E. Kelmer; D.G. Ohad; M.H. Shamir; O. Chai; S. Lavie; G.A. Sutton; I. Aroch; S. Klainbart (The Veterinary Journal, 2023)

Corrigendum: A trait‐based carbon export model for mesopelagic fishes in the Gulf of Mexico with consideration of asynchronous vertical migration, flux boundaries, and feeding guilds - Matthew S. Woodstock; Tracey T. Sutton; Yuying Zhang (Limnology and Oceanography, 2022)

Bridging the callosal gap in gait: corpus callosum white matter integrity’s role in lower limb coordination - Sutton B. Richmond; Daniel S. Peterson; Brett W. Fling (Brain Imaging and Behavior, 2022)

GeoSoilEnviroCARS (Sector 13) at the Advanced Photon Source: a comprehensive synchrotron radiation facility for Earth science research at ambient and extreme conditions - S. R. Sutton; M. L. Rivers; S. Chariton; P. J. Eng; A. Lanzirotti; M. Newville; T. Officer; V. B. Prakapenka; Y. J. Ryu; J. E. Stubbs; S. Tkachev; Y. Wang; et al. (Physics and Chemistry of Minerals, 2022)

A trait‐based carbon export model for mesopelagic fishes in the Gulf of Mexico with consideration of asynchronous vertical migration, flux boundaries, and feeding guilds - Matthew S. Woodstock; Tracey T. Sutton; Yuying Zhang (Limnology and Oceanography, 2022)
Fish‐mediated carbon export provides a significant proportion of the biological carbon pump in oligotrophic regions. Bioenergetic models estimate this carbon transport, but many lack species‐specific traits and no carbon export model has been developed in the mesopelagic Gulf of Mexico. Intensive mesopelagic sampling efforts in the northern and eastern Gulf of Mexico have provided high‐resolution information regarding community composition, species' vertical migratory characteristics, diel depth occupancies, and diets. A stochastic, individual‐based model was developed for deep‐pelagic fishes in the northern Gulf of Mexico to estimate bioenergetic rates and carbon export fluxes. Fishes that ate gelatinous zooplankton consumed more mass per body weight per day than predators of cephalopods and fishes, ostensibly to increase the throughput of prey with less carbon (gelata) or more refractory materials (Crustacea). A dynamic energy budget submodel indicated that during 81% of occurrences, asynchronous vertically migrating fishes rested for 1 d before migrating again, but migrations on successive days were possible. In terms of carbon export, myctophids and stomiids contributed greater than 53% and 12% of the active carbon flux for the entire assemblage in all scenarios. The assemblage‐wide carbon export rate driven by vertically migrating fishes was 0.14–0.72 mg C m −2 d −1 , 61% of the ingested carbon by the assemblage. Incorporating species‐specific traits and individual variability in bioenergetic models allows for more complex research questions (e.g., the effect of feeding guilds and asynchronous migration on carbon export) compared to the carbon export models that otherwise assume all fishes within a functional group are equivalent.

Environmental factors associated with Baylisascaris procyonis infection from a population of raccoons in Toronto, Ontario, Canada - Shannon K. French; David L. Pearl; William B. Sutton; Andrew S. Peregrine; Claire M. Jardine (Urban Ecosystems, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of environmental variables on a nearshore arctic fish community, 2001–2018 - J. T. Priest; F. J. Mueter; S. W. Raborn; T. M. Sutton (Polar Biology, 2022)

What the pluck? The theft of mammal hair by birds is an overlooked but common behavior with fitness implications - Henry S. Pollock; Sean E. MacDonald; Jeferson Vizentin‐Bugoni; Jeffrey D. Brawn; Zachary S. Sutton; Mark E. Hauber (Ecology, 2021)

The effect of shoe cushioning on gait and balance in females with multiple sclerosis - Andrew S. Monaghan; Patrick G. Monaghan; Sutton B. Richmond; Jamie A. Roper; Brett W. Fling (Experimental Brain Research, 2021)

Coastal Wetlands Exposure to Storm Surge and Waves in the Albemarle-Pamlico Estuarine System during Extreme Events - Felício Cassalho; Tyler W. Miesse; André de S. de Lima; Arslaan Khalid; Celso M. Ferreira; Ariana E. Sutton-Grier (Wetlands, 2021)

Fine-scale foraging effort and efficiency of Macaroni penguins is influenced by prey type, patch density and temporal dynamics - G. J. Sutton; C. A. Bost; A. Z. Kouzani; S. D. Adams; K. Mitchell; J. P. Y. Arnould (Marine Biology, 2021)

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Trends in Demand of Urban Surface Water Extractions and in Situ Use Functions - E. S. van der Meulen; N. B. Sutton; F. H. M. van de Ven; P. R. van Oel; H. H. M. Rijnaarts (Water Resources Management, 2020)
Scientific literature currently lacks comprehensive understanding of urban surface water use functions. This hampers sound analysis of the demand and potential supply of these functions. This study provides a comprehensive overview of potential use functions, by integrating knowledge from ecosystem services and integrated urban water management fields. Analysis of water-related management plans for Toronto and Amsterdam shows that surface water is currently being used for a variety of functions related to nutrition, energy, water regulation, recreation, symbolic use, transportation and floating buildings. Notably, many use functions involve in situ use, rather than water extractions. Interviewed water managers and spatial planners in both cities expect demand of most use functions to increase by 2040, especially demand for thermal energy extraction, recreation and transportation. Some identified novel demands, such as climate regulation and reuse of waste products from waterway maintenance. Increasing demand is mainly driven by urban growth, climate change and sustainability ambitions. This study found urban surface water uses that are usually not acknowledged in scientific literature on urban water management. This comprehensive overview supports planning, design, and maintenance of urban surface waters, laying the foundation for future research on supply and demand of urban water use functions.

Diet and parasites of a mesopelagic fish assemblage in the Gulf of Mexico - Matthew S. Woodstock; Christopher A. Blanar; Tracey T. Sutton (Marine Biology, 2020)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Unparalleled coupled ocean-atmosphere summer heatwaves in the New Zealand region: drivers, mechanisms and impacts - M. James Salinger; Howard J. Diamond; Erik Behrens; Denise Fernandez; B. Blair Fitzharris; Nicholas Herold; Paul Johnstone; Huub Kerckhoffs; A. Brett Mullan; Amber K. Parker; James Renwick; Claire Scofield; et al. (Climatic Change, 2020)

Virtual time-to-contact identifies balance deficits better than traditional metrics in people with multiple sclerosis - Tyler T. Whittier; Sutton B. Richmond; Andrew S. Monaghan; Brett W. Fling (Experimental Brain Research, 2020)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Hawaii Coastal Seawater CO2 Network: A Statistical Evaluation of a Decade of Observations on Tropical Coral Reefs - Gerianne J. Terlouw; Lucie A. C. M. Knor; Eric Heinen De Carlo; Patrick S. Drupp; Fred T. Mackenzie; Yuan Hui Li; Adrienne J. Sutton; Albert J. Plueddemann; Christopher L. Sabine (Frontiers in Marine Science, 2019)

Tropical Pacific Observing System - Neville Smith; William S. Kessler; Sophie Cravatte; Janet Sprintall; Susan Wijffels; Meghan F. Cronin; Adrienne Sutton; Yolande L. Serra; Boris Dewitte; Peter G. Strutton; Katherine Hill; Alex Sen Gupta; et al. (Frontiers in Marine Science, 2019)

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

Environmental evidence for a pygmy blue whale aggregation area in the Subtropical Convergence Zone south of Australia - Maria I. Garcia‐Rojas; K. Curt S. Jenner; Peter C. Gill; Micheline‐Nicole M. Jenner; Alicia L. Sutton; Robert D. McCauley (Marine Mammal Science, 2018)
The importance of the Subtropical Convergence Zone south of Australia as a feeding area to the pygmy blue whale of the eastern Indian Ocean was investigated to better understand migration patterns and habitat use. A combination of satellite tagging studies during 2003–2005 and acoustic and visual surveys during the austral summer of 2013 confirmed the presence of pygmy blue whales in the Subtropical Convergence Zone and provided evidence for feeding throughout the region. Of the 67 pygmy blue whales acoustically detected, many were localized in proximity to sea surface temperature fronts and high chlorophyll concentrations, which could be a behavioral strategy to attract conspecifics to good feeding sites. Aggregations of up to four pygmy blue whales, along with decreased call rates during the day, may suggest feeding despite no direct observations of pygmy blue whales consuming euphausiids. The oceanographic features present throughout the Subtropical Convergence Zone continue to create an environment productive enough to support the world's largest living mammals during their migratory foraging movements between the Southern Ocean and Indonesia.

Fungal Keratitis Secondary to Trametes betulina: A Case Report and Review of Literature - Joshua S. Hardin; Deanna A. Sutton; Nathan P. Wiederhold; James Mele; Sunali Goyal (Mycopathologia, 2017)

Recommendations for the future of recreational fisheries to prepare the social‐ecological system to cope with change - R. Arlinghaus; S. J. Cooke; S. G. Sutton; A. J. Danylchuk; W. Potts; K. de M. F. Freire; J. Alós; E. T. da Silva; I. G. Cowx; R. van Anrooy (Fisheries Management and Ecology, 2016)
This paper presents conclusions and recommendations that emerged from the 7th World Recreational Fishing Conference ( WRFC ) held in Campinas, Brazil in September 2014. Based on the recognition of the immense social and economic importance of recreational fisheries coupled with weaknesses in robust information about these fisheries in many areas of the world, particularly in many economies in transition, it is recommended to increase effort to build effective governance arrangements and improve monitoring and assessment frameworks in data‐poor situations. Moreover, there is a need to increase interdisciplinary studies that will foster a systematic understanding of recreational fisheries as complex adaptive social‐ecological systems. To promote sustainable recreational fisheries on a global scale, it is recommended the detailed suggestions for governance and management outlined in the United Nations Food and Agricultural Organization Technical Guidelines for Responsible Fisheries: Recreational Fisheries are followed.

Mapping recreational fishers’ informal learning of scientific information using a fuzzy cognitive mapping approach to mental modelling - O. Li; S. A. Gray; S. G. Sutton (Fisheries Management and Ecology, 2016)
Fisheries management benefits from improving the communication of scientific information to recreational fishers through improved compliance and greater contributions during consultation and engagement. This study uses fuzzy cognitive mapping to collect detailed, graphic information about recreational fishers’ mental models as a way to improve the way scientific information is communicated to them. Fishers were given three examples of scientific information to understand the affective, cognitive and conative reactions to different types of fisheries‐related information that they often encounter, and mental models were derived based on topics they found most and least interesting. This study identifies driving variables and constraints to fishers’ interest in taking up scientific information. The results suggest a message's clarity, perceived regular usefulness, good and bad emotion and investments in money and time influence fishers’ interest in taking up scientific information. Fishers’ initial levels of interest in a topic also significantly affect the complexity of thought processes leading to further interest in informal learning and the relative roles of the driving variables and constraints.

Stimulation of the subthalamic nucleus engages the cerebellum for motor function in parkinsonian rats - Alexander C. Sutton; Katherine A. O’Connor; Julie G. Pilitsis; Damian S. Shin (Brain Structure and Function, 2015)

High-resolution skim genotyping by sequencing reveals the distribution of crossovers and gene conversions in Cicer arietinum and Brassica napus - Philipp E. Bayer; Pradeep Ruperao; Annaliese S. Mason; Jiri Stiller; Chon-Kit Kenneth Chan; Satomi Hayashi; Yan Long; Jinling Meng; Tim Sutton; Paul Visendi; Rajeev K. Varshney; Jacqueline Batley; et al. (Theoretical and Applied Genetics, 2015)

Quantifying alosine prey in the diets of marine piscivores in the Gulf of Maine - S. P. McDermott; N. C. Bransome; S. E. Sutton; B. E. Smith; J. S. Link; T. J. Miller (Journal of Fish Biology, 2015)
The objectives of this work were to quantify the spatial and temporal distribution of the occurrence of anadromous fishes (alewife Alosa pseudoharengus , blueback herring Alosa aestivalis and American shad Alosa sapidissima ) in the stomachs of demersal fishes in coastal waters of the north‐west Atlantic Ocean. Results show that anadromous fishes were detectable and quantifiable in the diets of common marine piscivores for every season sampled. Even though anadromous fishes were not the most abundant prey, they accounted for c. 5–10% of the diet by mass for several marine piscivores. Statistical comparisons of these data with fish diet data from a broad‐scale survey of the north‐west Atlantic Ocean indicate that the frequency of this trophic interaction was significantly higher within spatially and temporally focused sampling areas of this study than in the broad‐scale survey. Odds ratios of anadromous predation were as much as 460 times higher in the targeted sampling as compared with the broad‐scale sampling. Analyses indicate that anadromous prey consumption was more concentrated in the near‐coastal waters compared with consumption of a similar, but more widely distributed species, the Atlantic herring Clupea harengus . In the context of ecosystem‐based fisheries management, the results suggest that even low‐frequency feeding events may be locally important, and should be incorporated into ecosystem models.

A Direct Pre-screen for Marine Bacteria Producing Compounds Inhibiting Quorum Sensing Reveals Diverse Planktonic Bacteria that are Bioactive - Jamie S. Linthorne; Barbara J. Chang; Gavin R. Flematti; Emilio L. Ghisalberti; David C. Sutton (Marine Biotechnology, 2015)

Vaccine Delivery to the Oral Cavity Using Coated Microneedles Induces Systemic and Mucosal Immunity - Yunzhe Ma; Wenqian Tao; Shelly J. Krebs; William F. Sutton; Nancy L. Haigwood; Harvinder S. Gill (Pharmaceutical Research, 2014)

Illustrating the critical role of human dimensions research for understanding and managing recreational fisheries within a social‐ecological system framework - L. M. Hunt; S. G. Sutton; R. Arlinghaus (Fisheries Management and Ecology, 2013)
Effective management of recreational fishing requires understanding fishers and their actions. These actions constitute critical links between social and ecological systems that result in outcomes that feedback and influence recreational fishers' actions and the management of these actions. Although much research exists on recreational fishers and their actions, this research is often disconnected from management issues. One way to help to overcome this disconnect is to illustrate how past research on the social component of recreational fishing fits within an emerging coupled social‐ecological system ( SES ) framework. Herein, a conceptual SES is first developed with specific attention to recreational fisheries. This SES is then used to illustrate the importance of considering human dimensions research for articulating, studying and ultimately managing key outcomes of recreational fisheries (e.g. fish population conservation, fisher well‐being) using the example of harvest regulations and a brief review of past interdisciplinary research on recreational fishing. The article ends by identifying key research needs including understanding: how factors such as management rules affect the diversity of actions by recreational fishers; how governance and management approaches adapt to changing social and resource conditions; and how recreational fishers learn and share information.

A verification framework for interannual-to-decadal predictions experiments - L. Goddard; A. Kumar; A. Solomon; D. Smith; G. Boer; P. Gonzalez; V. Kharin; W. Merryfield; C. Deser; S. J. Mason; B. P. Kirtman; R. Msadek; et al. (Climate Dynamics, 2013)

Internal waves downstream of Norfolk Ridge, western Pacific, and their biophysical implications - Craig L. Stevens; Philip J. H. Sutton; Cliff S. Law N (Limnology and Oceanography, 2012)
An 11‐d quasi‐Lagrangian surface layer experiment to the east of Norfolk Island tracked a 140‐m‐deep drifting vertical array (DVA) of instruments, including conductivity sensors, thermistors, and current meters. These are the first in situ data from the area to measure large‐amplitude internal waves. The observations show isotherm peak‐to‐peak excursions reaching 50 m and were dominated by the semidiurnal forcing frequency. The DVA exhibited horizontal loops at the semidiurnal tidal frequency as it tracked water at depths of 80‐140 m to within 10% of total horizontal displacement. The large vertical isotherm excursions generated substantial vertical shear. Temperature microstructure estimates of the vertical diffusivity of scalar properties at 70‐m depth, around the center of the thermocline, were on the order of 10 −4 m 2 s −1 and around an order of magnitude larger at shallower depths. When combined with nitrate data, this implies vertical fluxes of nitrate in the pycnocline of ∼ 1 mmol m −2 d −1 . The internal waves also potentially cause an interaction between the variability in tidal forcing and the diurnal radiation cycle that influences chlorophyll in the deep chlorophyll maximum. The average effect of the internal wave was to increase the light level for a particular isotherm over the static case. The internal wave‐induced velocities were strong enough to dominate phytoplankton rise speeds and so potentially played a role in the formation and persistence of an observed Trichodesmium bloom.

Polymorphic variants in tenascin-C (TNC) are associated with atherosclerosis and coronary artery disease - Mollie A. Minear; David R. Crosslin; Beth S. Sutton; Jessica J. Connelly; Sarah C. Nelson; Shera Gadson-Watson; Tianyuan Wang; David Seo; Jeffrey M. Vance; Michael H. Sketch; Carol Haynes; Pascal J. Goldschmidt-Clermont; et al. (Human Genetics, 2011)

Chemical and antimicrobial treatments change the viscoelastic properties of bacterial biofilms - Warren L. Jones; Michael P. Sutton; Ladean McKittrick; Philip S. Stewart (Biofouling, 2011)

Differences in water-use efficiency among perennial forages used by the dairy industry under optimum and deficit irrigation - J. S. Neal; W. J. Fulkerson; B. G. Sutton (Irrigation Science, 2010)

Bioaccumulation and biotransformation of decabromodiphenyl ether and effects on daily growth in juvenile lake whitefish (Coregonus clupeaformis) - Yin-Ming Kuo; Maria S. Sepúlveda; Trent M. Sutton; Hugo G. Ochoa-Acuña; Andrew M. Muir; Benjamin Miller; Inez Hua (Ecotoxicology, 2010)

Bioaccumulation and biomagnification of polybrominated diphenyl ethers in a food web of Lake Michigan - Yin-Ming Kuo; Maria S. Sepúlveda; Inez Hua; Hugo G. Ochoa-Acuña; Trent M. Sutton (Ecotoxicology, 2010)

In vitro and in vivo characterization of JNJ-31020028 (N-(4-{4-[2-(diethylamino)-2-oxo-1-phenylethyl]piperazin-1-yl}-3-fluorophenyl)-2-pyridin-3-ylbenzamide), a selective brain penetrant small molecule antagonist of the neuropeptide Y Y2 receptor - James R. Shoblock; Natalie Welty; Diane Nepomuceno; Brian Lord; Leah Aluisio; Ian Fraser; S. Timothy Motley; Steve W. Sutton; Kirsten Morton; Ruggero Galici; John R. Atack; Lisa Dvorak; et al. (Psychopharmacology, 2010)

Development of a low-cost system for measuring conditional time-averaged gradients of SO2 and NH3 - D. Famulari; D. Fowler; E. Nemitz; K. J. Hargreaves; R. L. Storeton-West; G. Rutherford; Y. S. Tang; M. A. Sutton; K. J. Weston (Environmental Monitoring and Assessment, 2010)

The evolution of two homologues of the core protein VP6 of epizootic haemorrhagic disease virus (EHDV), which correspond to the geographical origin of the virus - S. J. Anthony; K. E. Darpel; S. Maan; G. Sutton; H. Attoui; P. P. C. Mertens (Virus Genes, 2010)

Comparison of Outcomes of Permanently Closed and Periodically Harvested Coral Reef Reserves - C. Y. BARTLETT; C. MANUA; J. CINNER; S. SUTTON; R. JIMMY; R. SOUTH; J. NILSSON; J. RAINA (Conservation Biology, 2009)
In many areas of the developing world, the establishment of permanent marine reserves is inhibited by cultural norms or socioeconomic pressures. Community conserved areas that are periodically harvested are increasingly being implemented as fisheries management tools, but few researchers have empirically compared them with permanently closed reserves. We used a hierarchal control‐impact experimental design to compare the abundance and biomass of reef fishes, invertebrates, and substrate composition in periodically harvested and permanent reserves and in openly fished (control sites) of the South Pacific island country of Vanuatu. Fished species had significantly higher biomass in periodically harvested reserves than in adjacent openly fished areas. We did not detect differences in substratum composition between permanent reserves and openly fished areas or between permanent reserves and periodically harvested reserves. Giant clams (tridacnids) and top shells (Trochus niloticus) were vulnerable to periodic harvest, and we suggest that for adequate management of these species, periodically harvested community conservation areas be used in conjunction with other management strategies. Periodic harvest within reserves is an example of adaptive and flexible management that may meet conservation goals and that is suited to the social, economic, and cultural contexts of many coastal communities in the developing world .

Abundance and movement patterns of age-0 juvenile lake sturgeon in the Peshtigo River, Wisconsin - David C. Caroffino; Trent M. Sutton; Mark S. Lindberg (Environmental Biology of Fishes, 2009)

Consequences of injuries on survival and reproduction of common bottlenose dolphins ( Tursiops truncatus ) along the west coast of Florida - Randall S. Wells; Jason B. Allen; Suzanne Hofmann; Kim Bassos‐Hull; Deborah A. Fauquier; Nélio B. Barros; Ruth E. DeLynn; Gretchen Sutton; Victoria Socha; Michael D. Scott (Marine Mammal Science, 2008)
Accurate identification of human‐induced injuries that lead to death or interfere with reproduction is important for marine mammal management, as deaths exceeding established limits can lead to restrictions on fisheries or vessel operations. The fates of cetaceans last seen swimming with attached gear, particularly in pelagic fisheries, or with vessel strike lacerations, have been difficult to predict. Survival and reproduction data from long‐term research on resident common bottlenose dolphins near Sarasota, Florida were examined relative to consequences of fishing gear ingestion, line entanglements, vessel strikes, and amputations of unknown origins. Fishing hooks embedded in the throat, goosebeak, or esophagus, or line wrapped around the goosebeak, generally lead to death. Multiple, constrictive line wraps around fin insertions can lead to amputation, blood loss, impaired mobility, or infection. Dolphins with ingested gear or severe entanglements may swim away with the gear, but likely die later. Propeller injuries involving only soft tissue were often survivable. Some dolphins survived amputations of the distal ends of fins, and continued to reproduce. As a precautionary approach, dolphins with ingested gear or severe constrictive entanglements should be considered mortalities, but extrapolations of findings from coastal bottlenose dolphins to other cetaceans and different gear must be done with caution.

The Nightsat mission concept - C. D. Elvidge; P. Cinzano; D. R. Pettit; J. Arvesen; P. Sutton; C. Small; R. Nemani; T. Longcore; C. Rich; J. Safran; J. Weeks; S. Ebener (International Journal of Remote Sensing, 2007)

Biological control of pythium root rot of chrysanthemum in small-scale hydroponic units - W. Liu; J. C. Sutton; B. Grodzinski; J. W. Kloepper; M. S. Reddy (Phytoparasitica, 2007)

Focusing of phytodetritus deposition beneath a deep‐ocean front, Chatham Rise, New Zealand - Scott D. Nodder; Gerard C. A. Duineveld; Conrad A. Pilditch; Philip J. Sutton; P. Keith Probert; Marc S. S. Lavaleye; Rob Witbaard; F. Hoe Chang; Julie A. Hall; Ken M. Richardson (Limnology and Oceanography, 2007)
In October 2001, we observed a deep‐ocean phytodetritus deposition event on Chatham Rise beneath the Subtropical Front (STF). The origin of this phytodetritus was probably an extensive phytoplankton bloom that occurred in the STF in the preceding weeks. We assessed the spatial distribution of the deposition event using video images from benthic lander and epibenthic trawl deployments and sediment pigment analyses at six sites on a north—south transect across Chatham Rise. High surficial sediment chlorophyll a concentrations were restricted spatially to the southern flank of Chatham Rise (350–1,200‐m depth) with the highest values centered at ~750‐m water depth (750 S). This southern 750 S site was also the only site where macroscopic phytodetritus was observed, coincident with elevated benthic biomass and sediment community respiration rates. At 750 S, phytodetritus resuspension was observed on video and corroborated by current meter, sediment trap, and optical backscatter measurements, suggesting a threshold erosion current speed for phytodetritus of ~10 cm s −1 , equivalent to a shear velocity of 0.5 cm s −1 and similar to other deep‐ocean studies elsewhere. The restriction of macroscopic phytodetritus deposition to 750 S was related to a zone of current convergence within the STF and lower near‐bed current speeds observed across ~1‐day that promoted deposition. Observations of high benthic biomass and respiration on the southern flank of Chatham Rise suggest that this focusing process is important in fueling the energy demands of benthic communities, in association with the general west‐east advection of organic matter within the STF itself. Such physical focusing of labile organic matter deposition may be an important process in other highly productive frontal systems.

Exophiala xenobiotica sp. nov., an opportunistic black yeast inhabiting environments rich in hydrocarbons - G. S. De Hoog; J. S. Zeng; M. J. Harrak; D. A. Sutton (Antonie van Leeuwenhoek, 2006)

Comparison of COSPEC and two miniature ultraviolet spectrometer systems for SO2 measurements using scattered sunlight - Tamar Elias; A. Jeff Sutton; Clive Oppenheimer; Keith A. Horton; Harold Garbeil; Vitchko Tsanev; Andrew J. S. McGonigle; Glyn Williams-Jones (Bulletin of Volcanology, 2006)

Genetic analysis of adiponectin and obesity in Hispanic families: the IRAS Family Study - Beth S. Sutton; Stefanie Weinert; Carl D. Langefeld; Adrienne H. Williams; Joel K. Campbell; Mohammed F. Saad; Steven M. Haffner; Jill M. Norris; Donald W. Bowden (Human Genetics, 2005)

Regional Atmospheric Budgets of Reduced Nitrogen Over the British Isles Assessed Using a Multi-Layer Atmospheric Transport Model - N. Fournier; Y. S. Tang; U. Dragosits; Y. DE Kluizenaar; M. A. Sutton (Water, Air, & Soil Pollution, 2005)

Growth and survival of seedlings of native plants in an impoverished and highly disturbed soil following inoculation with arbuscular mycorrhizal fungi - G. S. Pattinson; K. A. Hammill; B. G. Sutton; P. A. McGee (Mycorrhiza, 2004)

Passive hinge forces in the feeding apparatus of Aplysia aid retraction during biting but not during swallowing - G. P. Sutton; J. B. Macknin; S. S. Gartman; G. P. Sunny; R. D. Beer; P. E. Crago; D. M. Neustadter; H. J. Chiel (Journal of Comparative Physiology A, 2004)

Species Richness and Invasion Vectors: Sampling Techniques and Biases - S. Gollasch; H. Rosenthal; H. Botnen; M. Crncevic; M. Gilbert; J. Hamer; N. Hülsmann; C. Mauro; L. McCann; D. Minchin; B. Öztürk; M. Robertson; et al. (Biological Invasions, 2003)

What motivates interest in attending a familial cancer genetics clinic? - L. Fraser; S. Bramald; C. Chapman; C. Chu; V. Cornelius; F. Douglas; A. Lucassen; A. Nehammer; S. Sutton; M. Trivella; S. Hodgson (Familial Cancer, 2003)

Bacterial degradation of arsenobetaine via dimethylarsinoylacetate - Richard O. Jenkins; Alisdair W. Ritchie; John S. Edmonds; Walter Goessler; Nathalie Molenat; Doris Kuehnelt; Christopher F. Harrington; Peter G. Sutton (Archives of Microbiology, 2003)

In vivo glycosylation of MUC1 in airway epithelial cells - Howard S. Silverman; Mark Sutton-Smith; Paul Heal; Simon Parry; Timea Palmai-Pallag; Shih-Hsing Leir; Howard R. Morris; Anne Dell; Ann Harris (Glycoconjugate Journal, 2002)

A case of segmental paternal isodisomy of chromosome 14 - Karen J. Coveler; Sam P. Yang; Reid V. Sutton; Jay M. Milstein; Yuan-Qing Wu; Cami Bois; Linda S. Beischel; John P. Johnson; Lisa G. Shaffer (Human Genetics, 2002)

Sustainable Management of Landfill Leachate by Irrigation - Mark S. Bowman; Timothy S. Clune; Bruce G. Sutton (Water, Air, & Soil Pollution, 2002)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Effects of Selective Logging on the Butterflies of a Bornean Rainforest - S. J. Willott; D. C. Lim; S. G. Compton; S. L. Sutton (Conservation Biology, 2000)
Selective logging has been the main cause of disturbance to tropical forests in Southeast Asia, so the extent to which biodiversity is maintained in selectively logged forest is of prime conservation importance. We compared the butterfly assemblages of Bornean primary rainforest to those of rainforest selectively logged 6 years previously. We sampled by means of replicated transects stratified into riverine and ridge forests and we included roads in the logged forest. There was a three‐fold variation in species richness and abundance over the 8‐month sampling period. More species and individuals were observed in the logged forest, although between‐replicate variability was high. Rarefied species richness was positively correlated with canopy openness within the range of disturbance levels encountered at our forest sites. Within families, there was no significant difference in the number of species between primary and logged forest. There was a significant difference in the relative abundance of species, but this was due largely to the abundance of one or two species. Community ordination separated the sites along a gradient of disturbance and revealed strong differences between riverine and ridge‐forest butterfly assemblages in primary forest that were obscured in logged forest. There was no evidence that logging has resulted in a change in the composition of the butterfly assemblages from species with a local distribution to more widespread species. We conclude that at a logged forest site in close proximity to primary forest, low intensities of logging do not necessarily reduce the species richness or abundance of butterflies, although assemblage composition is changed.

Influence of gelling agents on culture medium gel strength, water availability, tissue water potential, and maturation response in embryogenic cultures of Pinus strobus L. - K. Klimaszewska; M. bernier-Cardou; D. R. Cyr; B. C. S. Sutton (In Vitro Cellular & Developmental Biology - Plant, 2000)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Effects of acute expansion of plasma volume on cardiovascular and thermal function during prolonged exercise - S. M. Grant; H. J. Green; S. M. Phillips; J. R. Sutton (European Journal of Applied Physiology, 1997)

The clinical phcarmacology of single doses of otilonium bromide in healthy volunteers - J. A. Sutton; S. G. Kilminster; G. P. Mould (European Journal of Clinical Pharmacology, 1997)

Identification and analysis of an alcelaphine herpesvirus 1 (AHV-1) cDNA clone expressing a fusion protein recognized by AHV-1-neutralizing antisera - R. S. Lahijani; S. M. Sutton; R. B. Klieforth; W. P. Heuschele (Archives of Virology, 1995)

Operation Everest II: An indication of deterministic chaos in human heart rate variability at simulated extreme altitude - Yoshiharu Yamamoto; Richard L. Hughson; John R. Sutton; Charles S. Houston; Allen Cymerman; Ernest L. Fallen; Marked V. Kamath (Biological Cybernetics, 1993)

The acute and chronic toxicity of ten chlorinated organic compounds to the American flagfish (Jordanella floridae) - A. D. Smith; A. Bharath; C. Mallard; D. Orr; K. Smith; J. A. Sutton; J. Vukmanich; L. S. McCarty; G. W. Ozburn (Archives of Environmental Contamination and Toxicology, 1991)

Synthesis of nonlinear control surfaces by a layered associative search network - Andrew G. Barto; Charles W. Anderson; Richard S. Sutton (Biological Cybernetics, 1982)

Landmark learning: An illustration of associative search - Andrew G. Barto; Richard S. Sutton (Biological Cybernetics, 1981)

Associative search network: A reinforcement learning associative memory - Andrew G. Barto; Richard S. Sutton; Peter S. Brouwer (Biological Cybernetics, 1981)